peningkatan kemampuan motorik halus anak melalui kolase sisik ikan: improving children's fine motor skills through fish scale collage - Sulastri Sulastri; Syahrul Ismet (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is based on the suboptimal fine motor skills of children in activities involving eye and hand coordination, such as sticking, cutting, and arranging objects. This study aims to improve children's fine motor skills through collage activities using fish scales in early childhood at Asyifa Kindergarten, Seberang Musi District, Kepahiang Regency. The study uses the Classroom Action Research (CAR) method with the model from Kemmis and Mc Taggart which is implemented in two cycles. The research subjects are children aged 5-6 years at Asyifa Kindergarten, totaling 10 children. Data collection techniques are carried out through observation, documentation, and assessment of children's performance. Data analysis is carried out descriptively quantitatively and qualitatively. Before the study was conducted, there was only 1 child who was at the BSH value, after the study, the child's fine motor skills were at 40% because they had not reached the minimum completeness value, so the study was continued with cycle 2. After cycle 2, the child's fine motor skills increased to 80% in the second action, so the study was stopped because they had reached the minimum completeness value. This study concludes that fish scale collages can significantly improve children's fine motor skills, concentration, and interest in learning through engaging media utilizing natural materials from the surrounding environment. Keywords: fine motor skills, collage, fish scales, early childhood, Classroom Action Research.